DETERMINAN YANG MEMPENGARUHI OPINI AUDIT ATAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI SUMATERA UTARA - Telaumbanua, Erikson Andrianus; Triprlyono, Agus; Maisyarah, Renny (Transpublika Publisher, 2024)
This research aims to analyze the determinants that influence audit opinions on district/city government financial reports in North Sumatra in the form of the level of disclosure and audit findings on regional government financial reports. The number of samples used in this research was 33 Regency/City LKPD in North Sumatra province period 2019-2021. This research was processed using SPSS (Statistical Package for the Social Science) software version 26. The focus of the research is partial and simultaneous in the multiple linear regression research model. The results of this research show that partially the level of disclosure has no effect on audit opinion and audit findings have no effect on audit opinion, but simultaneously the level of disclosure and audit findings have an effect on audit opinion.